Peran Dinas Pariwisata, Pemuda dan Olahraga Kabupaten Lima Puluh Kota dalam Pembangunan Pariwisata di Destinasi Wisata Lembah Harau untuk Menjamin Pariwisata yang Berkelanjutan - Anwar, Hairul; Jumiati, Jumiati (PUBLICNESS: Journal of Public Administration Studies, 2025)
This research examines the role of the Tourism, Youth and Sports Office of Lima Puluh Kota Regency in sustainable tourism development in the Harau Valley and identifies supporting and inhibiting factors. Sustainable tourism development in this area is important given its potential as a model tourist destination that combines economic growth with environmental and socio-cultural preservation. The research used a descriptive qualitative approach with data collection techniques, including field observations, in-depth interviews, and documentation studies. Data analysis shows that the Tourism Office carries out five primary roles: manager, planner, regulator, coordinator, and stimulator in the area's development. Implementing these roles is supported by the advantages of natural tourism attractions, good accessibility, and the availability of supporting facilities. However, significant obstacles exist, such as a low understanding of sustainable tourism among stakeholders, a limited development budget, and weak coordination between sectors. Based on these findings, it is recommended that aspects of strategic planning be strengthened, the supervision system be improved, and local culture be promoted to realize sustainable tourism development in the Harau Valley.